Echoes of the Great Genocide and Documentation on the Pages of Periodical "Hayastan" - Karapetyan, Armen (History and Culture, 2022)
"Hayastan" daily entered the historical arena with the direct efforts and responsibility of General Andranik. The commander-in-chief felt that the Eastern Armenian periodicals did not adequately cover the life needs of the displaced Western Armenians. Well-known Western-Armenian prose writer VahanTotovents was appointed editor of the newspaper. Throughout its activities, the newspaper covered the whole process of the catastrophe of the Armenians of the West during the First World War, covering the tragedy in the provinces of the Armenians focusing on the memories of survivors and eyewitnesses.